Simplified Application of 3D Face Editing based on Feature Point Localization - Li, Xue (Journal of Theory and Practice of Engineering Science, 2024)
With the development of social economy, the public's pursuit of beauty is becoming increasingly high, and the medical beauty market is hot. The 3D plastic surgery simulation system can collect facial 3D data and demonstrate the postoperative simulation effect, promoting communication between patients and doctors. This article uses the principle of structured light 3D imaging to reconstruct three-dimensional facial information. The Dlib library is used to recognize facial feature points and combine them with depth information to obtain three-dimensional feature point information, which can automatically obtain the eyes, nose, mouth and other parts of the face. Design human-computer interaction software using Qt framework and VTK visual library to display and edit 3D faces. Through algorithm design, up to 2-3 parameters can be controlled and edited to achieve deformation beautification of each part. The edited 3D face can be used to measure the changes in size, area, volume, and other data of various parts for subsequent medical plastic surgery and cosmetic applications.